Jayantabhaṭṭa's interpretation of anumāna - Bandyopadhyay, Nandita (DSA (Sanskrit), Jadavpur University-series, 2004)
Study of inference in Nyāyamañjarī of Jayanta Bhaṭṭa, fl. 850-910, work on Nyaya philosophy